TEKNOLOGI DALAM PENDIDIKAN AGAMA ISLAM : MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - Nurrahma, Faizah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
The technological revolution has brought significant transformations in various aspects of life, including Islamic religious education. This study aims to analyze the impact of the technological revolution on improving the quality of learning in Islamic religious education in the digital era. The main focus is to explore how digital technology can be utilized to create more effective, interactive, and relevant learning methods to the needs of today's learners. The research approach used is a qualitative approach using the literature study method, where library materials are used as data sources for formulating research problems. The results of the study show that technology integration, such as digital-based learning applications, social media, and e-learning platforms, can increase learner engagement, expand access to learning resources, and encourage the development of 21st century competencies, such as critical thinking and collaboration. However, the study also found challenges such as low digital literacy of educators, limited technological infrastructure, and the potential for misuse of technology.